Chlorophyll as a measure of plant health: Agroecological aspects - Nikolić, Bogdan R; Pavlović, Danijela M; Đurović, Sanja; Waisi, Hadi; Marisavljević, Dragana; Anđelković, Ana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
As photosynthesis is the basic process during which light energy is absorbed and converted into organic matter, the importance of the plant pigment chlorophyll (a and b forms) as an intermediary in transformation of the absorbed solar energy and its activity in the process of photosynthesis and synthesis of organic substances in plants are crucial. Therefore, this paper provides an overview of methods for monitoring the optical activity of chlorophyll molecules and methods (non-destructive and destructive) for quantification of chlorophyll in plants. These methods are used to estimate the effects of different stress factors (abiotic, biotic and xenobiotic) on the efficiency of photosynthesis and bioproductivity, aiming to assess the impact that these limiting factors have on the yield of various cultivars. Also, those methods for analysis of chlorophyll optical activity and/or content are appropriate for assessing the reaction of weed species to different agricultural practices (mineral nutrition, treatment by herbicides, etc.) and studies of different aspects of weed ecophysiology and their influence on crop harvest.
Keywords: Plant health; Photosynthesis; Chlorophylls